A Roadmap for Controlled and Efficient n‐Type Doping of Self‐Assisted GaAs Nanowires Grown by Molecular Beam Epitaxy. (17th March 2016) - Orrù, Marta; Repiso, Eva; Carapezzi, Stefania; Henning, Alex; Roddaro, Stefano; Franciosi, Alfonso; Rosenwaks, Yossi; Cavallini, Anna; Martelli, Faustino; Rubini, Silvia
Abstract : N ‐type doping of GaAs nanowires has proven to be difficult because the amphoteric character of silicon impurities is enhanced by the nanowire growth mechanism and growth conditions. The controllable growth of n ‐type GaAs nanowires with carrier density as high as 10 20 electron cm −3 by self‐assisted molecular beam epitaxy using Te donors is demonstrated here. Carrier density and electron mobility of highly doped nanowires are extracted through a combination of transport measurement and Kelvin probe force microscopy analysis in single‐wire field‐effect devices. Low‐temperature photoluminescence is used to characterize the Te‐doped nanowires over several orders of magnitude of the impurity concentration. The combined use of those techniques allows the precise definition of the growth conditions required for effective Te incorporation. Abstract : The control of doping in semiconductor nanowires is a crucial issue in the design of reliable nanowire‐based devices. The complementary use of transport measurements, Kelvin probe force microscopy, and photoluminescence demonstrates efficiency and reliability of Te as donor impurity in GaAs nanowires grown by self‐assisted molecular beam epitaxy.